Chinese Medicine Formula Siwu-Yin Inhibits Esophageal Precancerous Lesions by Improving Intestinal Flora and Macrophage Polarization - Shi, Hui-Juan; Chen, Xuan-Yu; Chen, Xin-Ran; Wu, Zhong-Bing; Li, Jian-Yong; Sun, Ya-Qin; Shi, Dong-Xuan; Li, Jing (Frontiers in Pharmacology, 2022)
Siwu-Yin (SWY), a traditional Chinese medicinal formula, can replenish blood and nourish Yin. It was recorded in ancient Chinese medicine books in treating esophageal dysphagia, which has similar symptoms and prognosis with esophageal precancerous lesions and esophageal cancer. However, its effect has not been established in vivo. This study explores the antiesophageal cancer effect of SWY on rats with esophageal precancerous lesions. By performing 16S rRNA gene sequencing and metabolomics, it was suggested that SWY may improve the composition of intestinal flora of rats by regulating the synthesis and secretion of bile acids. In addition, flow cytometry results showed that SWY treatment modified tumor microenvironment by improving macrophage polarization and therefore inhibiting the occurrence of esophageal precancerous lesions.